A study on the buying behavior of Ilonggos of selected pre-need plans ([n.d.].)
For years now, the pre-need plan industry has been a significant stature particularly in the social and business stability. Companies in the city of Iloilo that offer these plans flourished despite the soaring economic crisis. This is a study of the buying behavior of Ilongos as regards pre-need plans such as educational/college, pension and memorial/internet. The researchers especially yearned to discern the factors affecting the buying decision of the holders. This research made use of only one set of questionnaires, which were given to eighty respondents obtained through purposive sampling. The results of the study reflected that demographic factors such as age, civil status, number of children and income directly affect Ilonggos' buying decision. It showed that Ilonggos tend to buy educational plans at ages 26 to 30 since at this age they are more likely to have children. They availed of pension plans also at ages 26 to 30 and memorial plans at ages 36 to 40. Furthermore, it also illuminated that majority of the plans availers are married individuals. Our study also showed that pre-need plan buyers, on the average have income of more than P10,000. On the other hand, the test conducted proved that educational attainment, occupation, and gender do not have a bearing on Ilonggos' buying decision. Instance of death in the family is one situation that affects their decision. Psychological factors too, were found to have direct relationship with Ilonggos' buying behavior. Motivating factors consist of increasing cost of education, cost of death and the desire not to burden family at old age. Willingness and perception were proven to be also related to their buying decision. Furthermore, willingness was found to be directly related to income and perception to educational attainment. Given the capacity, willingness and positive perception, Ilonggos will buy pre-need plans. Social and group forces was also established to be directly related to Ilongos' buying behavior. Friends, relatives and siblings are among the reference groups that directly influence their buying decision. The study also proved that members of one's household have a bearing as to whom plans are bought for. Attributes of pre-need plan providers too, influence Ilongos buying behavior. among those attributes, reliability of the company and amount of premium are the most considered factors. Attributes were found to be directly related with the manner plan is availed and the study as well showed that most Ilonggos avail of the plans through agents for convenience. Among the information sources, face to face contact is most favored by Ilonggos.
[Research Paper (B.A. 200 - Business Research)] -- Iloilo City : University of the Philippines Visayas - College of Management, [n.d.].